Hydrogen sulfide modulates chromatin remodeling and inflammatory mediator production in response to endotoxin, but does not play a role in the development of endotoxin tolerance. Issue 1 (December 2016) - Rios, Ester; Soriano, Francisco; Olah, Gabor; Gerö, Domokos; Szczesny, Bartosz; Szabo, Csaba
Abstract Background Pretreatment with low doses of LPS (lipopolysaccharide, bacterial endotoxin) reduces the pro-inflammatory response to a subsequent higher LPS dose, a phenomenon known as endotoxin tolerance. Moreover, hydrogen sulfide (H2 S), an endogenous gaseous mediator (gasotransmitter) can exert anti-inflammatory effects. Here we investigated the potential role of H2 S in the development of LPS tolerance. THP1 differentiated macrophages were pretreated with the H2 S donor NaHS (1 mM) or the H2 S biosynthesis inhibitor aminooxyacetic acid (AOAA, 1 mM). Methods To induce tolerance, cells were treated with a low concentration of LPS (0.5 μg/ml) for 4 or 24 h, and then treated with a high concentration of LPS (1 μg/ml) for 4 h or 24 h. In in vivo studies, male wild-type and CSE-/- mice were randomized to the following groups: Control (vehicle); Endotoxemic saline for 3 days before the induction of endotoxemia with 10 mg/kg LPS) mg/kg; Tolerant (LPS at 1 mg/kg for 3 days, followed LPS at 10 mg/kg). Animals were sacrificed after 4 or 12 h; plasma IL-6 and TNF-α levels were measured. Changes in histone H3 and H4 acetylation were analyzed by Western blotting. Results LPS tolerance decreased pro-inflammatory cytokine production. AOAA did not affect the effect of tolerance on reducing cytokine production. Treatment of the cells with the H2 S donor reduced cytokine production. Induction of the tolerance increased the acetylation of H3; AOAA reduced histone acetylation. H2 S donation increased histone acetylation. Tolerance did not affect the responses to H2 S with respect to histone acetylation. Conclusions In conclusion, both LPS tolerance and H2 S donation decrease LPS-induced cytokine production in vitro and modulate histone acetylation. However, endogenous, CSE-derived H2 S does not appear to play a significant role in the development of LPS tolerance.